The Use of Mini Project-Based Learning Media to Develop Collaboration Skills in First Grade Students at SDN Tanjungsari - Rokayah, Eroh; Sopandi, Wahyu; Hendriawan, Deri; Paridah, Nur (International Conference on Elementary Education, 2025)
21st century learning requires mastery of collaboration skills as part of the 4C competencies (critical thinking, creativity, collaboration, communication) that are important for future learning success. However, initial observations at SDN Tanjungsari in Pabuaran District show that first-grade students remain passive and struggle to collaborate effectively in completing group tasks, highlighting the need for improved learning strategies. This study aims to analyze the improvement of students' collaboration skills through the use of mini-project-based learning media designed in accordance with the principles of social constructivism, where knowledge is built through interaction and cooperation among students. The research method used is quantitative with a one-group pretest-posttest pre-experimental design. The research subjects consisted of 25 first-grade students. Data were collected using a collaboration skills observation sheet and analyzed using a paired sample t-test. The results showed a significantincrease in students' collaboration skills after the implementation of mini-project media, with the average score increasing from 63.4 to 82.8 (p < 0.05). These findings confirm that simple and contextual project activities, such as creating collages and posters with environmental themes, are effective in fosteringresponsibility, communication, and cooperation. The implications of this study emphasize the importance of applying a mini-project-based learning approach as a strategy for integrating collaborative values from the elementary school level in order to realize active, meaningful, and participatory 21st-century learning.